Complete mitochondrial genome of Syzygium samarangense reveals genomic recombination, gene transfer, and RNA editing events - Lu, Guilong; Li, Qing (Frontiers in Plant Science, 2024)
Wax apple (Syzygium samarangense) is a commercial fruit that belongs to one of the most species-rich tree genera in the world. We report here the first complete S. samarangense mitogenome obtained using a hybrid assembly strategy. The mitogenome was a 530,242 bp circular molecule encoding 61 unique genes accounting for 7.99% of the full-length genome. Additionally, 167 simple sequence repeats, 19 tandem repeats, and 529 pairs of interspersed repeats were identified. Long read mapping and Sanger sequencing revealed the involvement of two forward repeats (35,843 bp and 22,925 bp) in mediating recombination. Thirteen homologous fragments in the chloroplast genome were identified, accounting for 1.53% of the mitogenome, and the longest fragment was 2,432 bp. An evolutionary analysis showed that S. samarangense underwent multiple genomic reorganization events and lost at least four protein-coding genes (PCGs) (rps2, rps7, rps11, and rps19). A total of 591 RNA editing sites were predicted in 37 PCGs, of which nad1-2, nad4L-2, and rps10-2 led to the gain of new start codons, while atp6-1156, ccmFC-1315 and rps10-331 created new stop codons. This study reveals the genetic features of the S. samarangense mitogenome and provides a scientific basis for further studies of traits with an epistatic basis and for germplasm identification.